Hoje é dia de visita: o testemunho carcerário brasileiro do início do século XXI - Scapini, Carla Zanatta (2015)
In Brazil, where it can be found a split by opposing forces, influenced on the one hand, by the growing struggle of certain groups to respect their fundamental rights and on the other hand, the conservative and reactionary dimensions occupying a hegemonic place in almost all sectors of social life, political and cultural comes a literary production that catalyzes these tensions in the form of narrative discourse. Modest, without the presumption to explain the phenomena of social exclusion and without the glamor of the word that can afford to transform everyday reality in pure delight, gender testimony is fixed in the Brazilian publishing market alongside other many aspects of heterogeneous contemporary literature. Coming from a Latin American tradition, engaged in rescuing the voice and the group stories versions saw their neglected worldview since the continent colonization, some early twenty-first century testimonies turn to the representation of the common prisoners life experiences, using the most varied narrative resources that go beyond the old dichotomy fact/fiction; communicative function/aesthetic function. The corpus of this study, in particular, are the narratives: Memórias de um sobrevivente, by Luiz Alberto Mendes; Cela forte mulher by Antonio Carlos Prado; andEstação Carandiru, by Drauzio Varella, produced from the authors actual experience in the prison area and concerned primarily on bringing out the prisoners‟ voice and their perspectives. The main purpose of these reports is to return the existence (at least in the culture sphere) to those whose experience, was denied by hegemonic society sectors, it is the basic point in the debate about violence and public safety. This study starts, therefore, with the political and cultural representation debate in the testimonial narrative from the individuals lives convicted of common crimes, consisting of these two great forces: on the one hand, a committed and supportive practice with the rescue of complexity of the story involved by diversity and by the clash of world views and on the other hand, a hegemonic vision that fights to keep its place naturally comfortable and seemingly harmonious. By Given this context of political and cultural disputes, this thesis aims to understand how the three testimonies occupy a place in the debate about crime and the prison universe and how they contribute to a more complex view and also more human, from the prisioners represented, providing the reader to develop a more empathetic view towards the otherness.